Defect reduced selectively grown GaN pyramids as template for green InGaN quantum wells. Issue 1 (4th December 2015) - Wagner, J.; Wächter, C.; Wild, J.; Müller, M.; Metzner, S.; Veit, P.; Schmidt, G.; Jetter, M.; Bertram, F.; Zweck, J.; Christen, J.; Michler, P.
Abstract: Abstractauthoren We report the growth of green emitting InGaN quantum wells (QWs) by metal‐organic vapor‐phase epitaxy (MOVPE) on three‐dimensional GaN templates. The 10 overbar 1 1 facets of GaN pyramids, fabricated by selective‐area growth (SAG), reduce the influence of the quantum‐confined Stark effect (QCSE) on the emission properties of the QW. The luminescence properties of a QW are a good indicator for the crystalline quality of the GaN layer beneath. Especially the presence of voids inside the pyramids, as well as stacking faults (SFs) and threading dislocations (TDs) in the wing region strongly influence the strain situation and the incorporation of In into the overlying InGaN layer. Thus, the crystal quality of the GaN pyramid has a strong influence on the efficiency and the emission properties of the active region. Therefore, a low‐temperature nucleation on the GaN buffer in conjunction with a decreasing Ga‐flux taking the decreasing c‐plane growth surface of the pyramid into account was introduced. The low‐temperature photoluminescence (PL) properties of the InGaN QW reveal the differences between the standard formation of the pyramid and this modified growth. Cathodoluminescence (CL) and transmission electron microscopy (TEM) measurements confirm the differences between the two growth modes in the crystal quality of the inner part of the pyramid.